2019
DOI: 10.1136/annrheumdis-2019-215328
|View full text |Cite
|
Sign up to set email alerts
|

Medications associated with fracture risk in patients with rheumatoid arthritis

Abstract: ObjectiveTo examine the fracture risk with use of disease-modifying antirheumatic drugs (DMARDs), statins, proton pump inhibitors (PPIs), opioids, non-opioid analgesics and psychotropic medications in a US-wide observational rheumatoid arthritis (RA) cohort.MethodsPatients with RA without prior fracture from 2001 through 2017 in FORWARD, a longitudinal observational registry, were assessed for osteoporosis-related site fractures (vertebra, hip, forearm and humerus). DMARD exposure was assessed in four mutually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 46 publications
5
79
0
Order By: Relevance
“…These findings were published in the August 2019 issue of the Annals of the Rheumatic Diseases . Certainly, the findings of Ozen et al 5 will be significant for clinicians; however, four points remain unaddressed that we would like to communicate with the authors.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These findings were published in the August 2019 issue of the Annals of the Rheumatic Diseases . Certainly, the findings of Ozen et al 5 will be significant for clinicians; however, four points remain unaddressed that we would like to communicate with the authors.…”
mentioning
confidence: 94%
“…In particular, statins may influence bone metabolism by increasing bone formation 3 4. Recently, Ozen et al 5 reported that medication with opioids, selective serotonin reuptake inhibitors, and glucocorticoids were associated with an increased risk of osteoporosis-related site fractures (vertebra, hip, forearm and humerus) in patients with rheumatoid arthritis, whereas statins and tumour necrosis factor-α inhibitors were associated with a decreased risk of vertebral fractures. These findings were published in the August 2019 issue of the Annals of the Rheumatic Diseases .…”
mentioning
confidence: 99%
“…1 Recently, a cohort study in USA conducted by Ozen et al published in the Annals of the Rheumatic Diseases reported that proton pump inhibitors therapy was not associated with increased fracture risk in patients with rheumatoid arthritis (HR=0.92; 95% CI 0.80 to 1.06). 2 Ozen et al's study is an important one and deserves a practical value. Some points not shown in the original article are shared with the readers.…”
mentioning
confidence: 96%
“…Table 1 shows that the incidence of major osteoporotic fractures is 1.33-fold higher in patients with proton pump inhibitors therapy than those without use, but it does not reach statistic significance (1.24 vs 0.94 per 100 person-years; 95% CI 0.86 to 2.06, p=0.2049) which was compatible with Ozen et al's study reporting that no association could be observed between proton pump inhibitors therapy and fracture risk in patients with rheumatoid arthritis. 2 Second, previous research has suggested that no significant association can be detected between proton pump inhibitors therapy and fracture risk in older adults. 4 Ozen et al's and our studies further confirm that even in patients with rheumatoid arthritis, such an association still does not exist.…”
mentioning
confidence: 99%
“…In another study, published in the Annals of Rheumatic Diseases, researchers looked at the fracture risk of several drugs often used alongside disease modifying antirheumatic drugs, including statins, proton pump inhibitors, opioids, non-opioid analgesics, and psychotropic drugs 3…”
mentioning
confidence: 99%